High-strength corrosion-resistant aluminum material and preparation method thereof
By using microcapsule corrosion inhibitors prepared by using chitosan and amino acid corrosion inhibitors on aluminum alloy profiles, combining dopamine layer and epoxy resin coatings, a multi-layer protective film is formed, which solves the problem of easy oxidation and corrosion of aluminum alloy profiles in harsh environments, and significantly improves its corrosion resistance and durability.
Patent Information
- Application Number
- CN202510065442.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Existing aluminum alloy profiles are prone to oxidation and corrosion in harsh environments, resulting in material deterioration and structural damage, and insufficient strength and durability, affecting service life and engineering benefits.
Using chitosan corrosion inhibitor and amino acid corrosion inhibitor as core components, a microcapsule corrosion inhibitor is prepared through condensation reaction and click reaction, combined with a dopamine layer, added to the epoxy resin to form a coating, coated on the surface of the aluminum profile and cured to form a multi-layer protective film.
It significantly improves the corrosion resistance, durability and crack resistance of aluminum profiles, extends the material's service cycle, reduces maintenance and replacement costs, and improves the economic benefits of the project.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum alloys, and in particular to a high-strength corrosion-resistant aluminum material and a preparation method thereof. Background Art
[0002] Aluminum alloy profiles have significant modern value in modern industry and construction due to their unique properties and advantages. The following is a detailed description of the modern value of aluminum alloy profiles:
[0003] 1. Aluminum alloy profiles have become an important choice of modern engineering materials due to their light weight and high strength. Compared with traditional steel, aluminum alloy has a lower density but higher strength and rigidity. This enables aluminum alloy profiles to achieve higher load-bearing capacity and longer service life in the fields of building structures, transportation, etc., while reducing overall weight and energy consumption.
[0004] 2. Aluminum alloy profiles have good machinability and can be processed through a variety of processes such as extrusion, casting, forging, etc. This makes aluminum alloy profiles suitable for various complex geometric shapes and structural designs. The development of modern CNC machining technology has further improved the machining accuracy and efficiency of aluminum alloy profiles, meeting the needs of high-end manufacturing and precision engineering.
[0005] 3. Aluminum alloy profiles are recyclable materials with significant environmental advantages. The recycling and reuse of aluminum consumes less energy and does not affect its performance, which meets the requirements of modern society for sustainable development and circular economy. The extensive use of aluminum alloy profiles helps reduce dependence on limited resources, reduce environmental pollution, and promote the development of green buildings and green transportation.
[0006] Aluminum alloy profiles are widely used in the fields of construction, transportation, aerospace, etc., and their service life directly affects the overall benefits of engineering projects. Improving corrosion resistance can effectively prevent oxidation and corrosion of aluminum alloys in harsh environments, and reduce material degradation and structural damage caused by corrosion. Enhancing strength and durability can resist external impact and fatigue damage, extend the service life of materials, reduce maintenance and replacement costs, and improve the economic benefits of projects.
[0007] In order to overcome the defects of the prior art, the present invention provides a high-strength corrosion-resistant aluminum material and a preparation method thereof. Summary of the invention
[0008] The object of the present invention is to provide a high-strength corrosion-resistant aluminum material and a preparation method thereof to solve the problems in the prior art.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0010] A method for preparing a high-strength corrosion-resistant aluminum material comprises the following steps:
[0011] Step 1: Mix chitosan corrosion inhibitor, amino acid corrosion inhibitor, polysulfone and dichloromethane, stir well to obtain an oil phase; then prepare a surfactant solution as an aqueous phase, slowly drop the oil phase into the aqueous phase, stir evenly to obtain a pre-emulsion, then stir and evaporate dichloromethane at 35-40°C, and filter, wash with water, wash with alcohol, filter and dry to obtain a microcapsule corrosion inhibitor; add the microcapsule corrosion inhibitor to the dopamine solution, stir and react for 10-15 hours, wash with water, wash with alcohol, filter and dry after the reaction to obtain a dopamine microcapsule corrosion inhibitor;
[0012] Step 2: Add dopamine microcapsule corrosion inhibitor to preheated epoxy resin, then add curing agent and stir for 20-30 minutes to obtain epoxy resin coating; take aluminum profile, grind, alcohol wash, immerse in dopamine solution for 10-15 hours, then apply epoxy resin coating and cure at 60-70℃ for 8-10 hours to obtain the finished product.
[0013] More optimally, in step one, the reaction mass ratio of chitosan corrosion inhibitor, amino acid corrosion inhibitor and polysulfone is (1.2-1.5):1:1.
[0014] More optimally, in step one, the preparation process of the chitosan corrosion inhibitor is as follows: chitosan is added to an acetic acid solution to swell for 1-2 hours, and then a 2-pyridine formaldehyde solution is added, the temperature is raised to 80-90°C for reaction for 6-8 hours, and after the reaction is completed, the pH is adjusted, suction filtration, alcohol washing, and vacuum drying are performed to obtain Schiff alkalinized chitosan; 8-hydroxyquinoline, concentrated hydrochloric acid, and formaldehyde solution are mixed, and hydrogen chloride gas is continuously introduced at 25-28°C for stirring and reaction for 10-12 hours. After the reaction is completed, suction filtration, washing, and vacuum drying are performed to obtain chlorohydroxyquinoline; Schiff alkalinized chitosan is added to an acetic acid solution to swell for 1-2 hours, and then chlorohydroxyquinoline is added, the temperature is raised to 80-90°C for reaction for 20-25 hours, and after the reaction is completed, the pH is adjusted, suction filtration, alcohol washing, and vacuum drying are performed to obtain the chitosan corrosion inhibitor.
[0015] More optimally, when preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridinecarboxaldehyde is 1: (4.0-4.5); when preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid and formaldehyde solution is 1: (1.0-1.2): 1; when preparing chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline is 1: (1.1-1.2); the concentration of the acetic acid solution is 3-5wt%; the concentration of the concentrated hydrochloric acid is 36.5-37wt%, and the concentration of the formaldehyde solution is 37-40wt%.
[0016] More optimally, in step one, the preparation process of the amino acid corrosion inhibitor is as follows: cysteine, sodium hydroxide and anhydrous ethanol are mixed, terephthalaldehyde solution is added dropwise at 30-40°C, and the mixture is stirred sufficiently until the solid no longer increases. After the reaction is completed, the mixture is cooled, washed with alcohol, and ground to obtain a Schiff-based amino acid; modified graphene, Schiff-based amino acid, 1173 photoinitiator and anhydrous ethanol are mixed, and the mixture is reacted under ultraviolet light for 10-20 minutes. After the reaction is completed, the mixture is extracted, dried, filtered, rotary evaporated, and vacuum dried to obtain an amino acid corrosion inhibitor.
[0017] More optimally, when preparing Schiff-based amino acids, the reaction molar ratio of cysteine, sodium hydroxide and terephthalaldehyde is (1.8-2.0): 1:1; when preparing amino acid corrosion inhibitors, the reaction molar ratio of C=C of modified graphene and the thiol group of Schiff-based amino acids is 1: (1.5-2.0); the amount of the 1173 photoinitiator used accounts for 4-5wt%.
[0018] More optimally, the preparation process of modified graphene is as follows: graphene oxide and anhydrous ethanol are mixed, and after ultrasonic dispersion, γ-methacryloxypropyltrimethoxysilane is added, and the mixture is refluxed at 110-120°C for 10-12h. After the reaction, the modified graphene is obtained by filtration, washing, and freeze-drying; wherein the reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane is (0.2-0.3):3.
[0019] More optimally, in step 1, lignin sulfonate is dissolved in water to obtain a surfactant solution with a concentration of 1.5-1.8 wt %.
[0020] More optimally, in step 1 or step 2, the pH value of the dopamine solution is 7.5-8.0, and the concentration is 1.2-1.5 g / L.
[0021] More optimally, in step 2, the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin, and curing agent is (0.2-0.3):3:1.
[0022] Beneficial effects of the present invention:
[0023] The characteristics of the present invention are that green and environmentally friendly chitosan is used as the main raw material, and the amino groups on the surface of chitosan and 2-pyridine formaldehyde are used to undergo a condensation reaction to generate Schiff-base chitosan; further, the prepared chlorohydroxyquinoline and the hydroxyl groups on the surface of Schiff-base chitosan undergo a substitution reaction to obtain a chitosan corrosion inhibitor. The Schiff base structure in the chitosan corrosion inhibitor can form a stable chelate with metal ions, which helps to form a protective film on the metal surface to prevent the corrosive medium (such as water, acid, alkali, etc.) from directly contacting the metal, and has good corrosion resistance; the nitrogen atoms in the pyridine structure can form coordination bonds with metal ions, enhance the adhesion of the corrosion inhibitor on the metal surface, and further improve the corrosion resistance; the chlorohydroxyquinoline component has a strong chelating ability and can form a stable chelate with metal ions to effectively prevent the corrosion process. In summary, the chitosan corrosion inhibitor can form a multi-layer protective film on the metal surface by combining a variety of corrosion-resistant structures, effectively preventing the erosion of the corrosive medium, and showing excellent comprehensive corrosion resistance.
[0024] The characteristics of the present invention are that biomass cysteine is used as the main raw material, and the amino group on the surface of cysteine and terephthalaldehyde undergo a condensation reaction to generate Schiff-base amino acids; further, the modified graphene with C=C and the thiol group on the surface of the Schiff-base amino acids undergo a click reaction to prepare an amino acid corrosion inhibitor. On the one hand, the Schiff base structure in the amino acid corrosion inhibitor has good corrosion resistance; on the other hand, the modified graphene can form a continuous and dense protective film on the metal surface, effectively isolating the corrosive medium and providing long-term corrosion protection; in addition, the high strength and stiffness of graphene can effectively enhance the mechanical properties of the material, making it less likely to be deformed and damaged when subjected to external forces, and showing better durability and crack resistance.
[0025] In step one, a microcapsule corrosion inhibitor is prepared using chitosan corrosion inhibitor and amino acid corrosion inhibitor as core materials and polysulfone as wall materials, and a dopamine layer is introduced into the outer wall of the capsule to prepare a dopamine microcapsule corrosion inhibitor. In step two, the dopamine microcapsule corrosion inhibitor and curing agent are added to the epoxy resin to obtain an epoxy resin coating; the epoxy resin coating is applied to the surface of the aluminum profile pretreated with dopamine to obtain a finished product. The dopamine layer on the surface of the microcapsule corrosion inhibitor has a synergistic enhancement effect on the surface corrosion resistance of the aluminum profile. In addition, a tighter fit can be achieved between the aluminum profile pretreated with dopamine and the epoxy resin coating layer to which the dopamine microcapsule corrosion inhibitor is added, thereby significantly improving the interfacial bonding strength and effectively reducing the risk of coating peeling. In summary, the finished product prepared by the present invention has good corrosion resistance, durability and crack resistance. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Source of raw materials:
[0028] Chitosan is provided by Shanghai McLean Biochemical Technology Co., Ltd. with the specification of AR; graphene oxide is provided by Hebei Ruihuang Metal Materials Co., Ltd. with the particle size of 35000 mesh; polysulfone is provided by Dalian Polysulfone Plastic Co., Ltd. with the specification of industrial grade; lignin sulfonate is provided by Nanjing Shanhu Chemical Co., Ltd. with the mass fraction of 98wt%; epoxy resin is provided by Shanghai Haoren International Trade Co., Ltd. with the model of 1009; curing agent is provided by Jinan Chenghao Chemical Co., Ltd. with the model of T-31.
[0029] Example 1: Step 1: Add chitosan to an acetic acid solution with a concentration of 5wt% and swell for 2h, then add 2-pyridine formaldehyde solution, heat to 90°C and react for 8h, adjust pH, filter, wash with alcohol, and vacuum dry after the reaction to obtain Schiff alkalinized chitosan; mix 8-hydroxyquinoline, concentrated hydrochloric acid with a concentration of 36.5wt% and formaldehyde solution with a concentration of 37wt%, continue to introduce hydrogen chloride gas at 28°C and stir for 12h, filter, wash, and vacuum dry after the reaction to obtain chlorohydroxyquinoline; add Schiff alkalinized chitosan to The mixture was added to an acetic acid solution with a concentration of 5wt% and swelled for 2h, and then chlorohydroxyquinoline was added, and the temperature was raised to 90°C for reaction for 25h. After the reaction, the pH was adjusted, the mixture was filtered, washed with alcohol, and dried in vacuo to obtain a chitosan corrosion inhibitor. When preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridinecarboxaldehyde was 1:4.3. When preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid, and formaldehyde solution was 1:1.1:1. When preparing the chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline was 1:1.2.
[0030] Cysteine, sodium hydroxide and anhydrous ethanol were mixed, and terephthalaldehyde solution was added dropwise at 40°C, and the mixture was stirred until the solid stopped increasing. After the reaction, the mixture was cooled, washed with alcohol and ground to obtain Schiff-based amino acid. Graphene oxide was mixed with anhydrous ethanol, and after ultrasonic dispersion, γ-methacryloxypropyltrimethoxysilane was added. The mixture was refluxed at 120°C for 12 hours. After the reaction, the mixture was filtered, washed and freeze-dried to obtain modified graphene. The modified graphene, Schiff-based amino acid, 1173 photoinitiator and anhydrous ethanol were mixed and subjected to ultraviolet. The reaction was carried out under light irradiation for 20 minutes. After the reaction was completed, the amino acid corrosion inhibitor was obtained by extraction, drying, filtering, rotary evaporation and vacuum drying. When preparing the Schiff-based amino acid, the reaction molar ratio of cysteine, sodium hydroxide and terephthalaldehyde was 1.9:1:1. When preparing the amino acid corrosion inhibitor, the reaction molar ratio of C=C of the modified graphene and the thiol group of the Schiff-based amino acid was 1:1.7. The amount of the 1173 photoinitiator was 5wt%; wherein the reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane was 0.3:3.
[0031] Chitosan corrosion inhibitor, amino acid corrosion inhibitor, polysulfone and dichloromethane are mixed and stirred to obtain an oil phase; lignin sulfonate is dissolved in water to obtain a 1.8wt% surfactant solution as an aqueous phase, the oil phase is slowly added dropwise to the aqueous phase, and the pre-emulsion is uniformly stirred, and the dichloromethane is evaporated by stirring at 40°C, and the microcapsule corrosion inhibitor is obtained by filtering, washing with water, washing with alcohol, filtering and drying; the microcapsule corrosion inhibitor is added to the dopamine solution, stirred for reaction for 15 hours, and after the reaction is completed, the dopamine microcapsule corrosion inhibitor is obtained by washing with water, washing with alcohol, filtering and drying; the reaction mass ratio of chitosan corrosion inhibitor, amino acid corrosion inhibitor and polysulfone is 1.3:1:1; the pH value of the dopamine solution is 7.5, and the concentration is 1.5g / L;
[0032] Step 2: Add dopamine microcapsule corrosion inhibitor to the preheated epoxy resin, then add curing agent and stir for 30 minutes to obtain epoxy resin coating; take the aluminum profile, grind, alcohol wash, and immerse in dopamine solution for 15 hours, then apply epoxy resin coating and cure at 70°C for 10 hours to obtain the finished product; the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin, and curing agent is 0.3:3:1.
[0033] Example 2: Step 1: chitosan was added to an acetic acid solution with a concentration of 5wt% and swelled for 1.5h, and then a 2-pyridine formaldehyde solution was added, and the temperature was raised to 85°C for reaction for 7h. After the reaction was completed, the pH was adjusted, filtered, washed with alcohol, and vacuum dried to obtain Schiff alkalinized chitosan; 8-hydroxyquinoline, concentrated hydrochloric acid with a concentration of 36.5wt% and formaldehyde solution with a concentration of 37wt% were mixed, and hydrogen chloride gas was continuously introduced at 27°C for stirring and reacting for 11h. After the reaction was completed, the mixture was filtered, washed, and vacuum dried to obtain chlorohydroxyquinoline; Schiff alkalinized chitosan was added to The mixture was added to an acetic acid solution with a concentration of 5wt% and swelled for 1.5h, and then chlorohydroxyquinoline was added, and the temperature was raised to 85°C for reaction for 23h. After the reaction, the pH was adjusted, the mixture was filtered, washed with alcohol, and dried in vacuo to obtain a chitosan corrosion inhibitor. When preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridinecarboxaldehyde was 1:4.3. When preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid, and formaldehyde solution was 1:1.1:1. When preparing the chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline was 1:1.2.
[0034] Cysteine, sodium hydroxide and anhydrous ethanol were mixed, and terephthalaldehyde solution was added dropwise at 35°C, and the mixture was stirred until the solid stopped increasing. After the reaction, the mixture was cooled, washed with alcohol and ground to obtain Schiff-based amino acid. Graphene oxide was mixed with anhydrous ethanol, and after ultrasonic dispersion, γ-methacryloxypropyltrimethoxysilane was added. The mixture was refluxed at 115°C for 11 hours. After the reaction, the mixture was filtered, washed and freeze-dried to obtain modified graphene. The modified graphene, Schiff-based amino acid, 1173 photoinitiator and anhydrous ethanol were mixed and subjected to ultraviolet. The reaction was carried out under light irradiation for 15 minutes. After the reaction was completed, the amino acid corrosion inhibitor was obtained by extraction, drying, filtering, rotary evaporation and vacuum drying. When preparing the Schiff-based amino acid, the reaction molar ratio of cysteine, sodium hydroxide and terephthalaldehyde was 1.9:1:1. When preparing the amino acid corrosion inhibitor, the reaction molar ratio of C=C of the modified graphene and the thiol group of the Schiff-based amino acid was 1:1.7. The amount of the 1173 photoinitiator was 5wt%. The reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane was 0.3:3.
[0035] Chitosan corrosion inhibitor, amino acid corrosion inhibitor, polysulfone and dichloromethane are mixed and stirred to obtain an oil phase; lignin sulfonate is dissolved in water to obtain a 1.8wt% surfactant solution as an aqueous phase, the oil phase is slowly added dropwise to the aqueous phase, and the pre-emulsion is uniformly stirred, and the dichloromethane is evaporated by stirring at 37°C, and the microcapsule corrosion inhibitor is obtained by filtering, washing with water, washing with alcohol, filtering and drying; the microcapsule corrosion inhibitor is added to the dopamine solution, stirred for reaction for 13 hours, and after the reaction is completed, the dopamine microcapsule corrosion inhibitor is obtained by washing with water, washing with alcohol, filtering and drying; the reaction mass ratio of chitosan corrosion inhibitor, amino acid corrosion inhibitor and polysulfone is 1.3:1:1; the pH value of the dopamine solution is 7.5, and the concentration is 1.5g / L;
[0036] Step 2: Add dopamine microcapsule corrosion inhibitor to the preheated epoxy resin, then add curing agent and stir for 25 minutes to obtain epoxy resin coating; take the aluminum profile, grind, alcohol wash, and immerse in dopamine solution for 13 hours, then apply epoxy resin coating and cure at 65°C for 9 hours to obtain the finished product; the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin and curing agent is 0.3:3:1.
[0037] Example 3: Step 1: Add chitosan to an acetic acid solution with a concentration of 5wt% and swell for 1h, then add 2-pyridine formaldehyde solution, heat to 80°C and react for 6h, adjust pH, filter, wash with alcohol, and vacuum dry after the reaction to obtain Schiff alkalinized chitosan; mix 8-hydroxyquinoline, concentrated hydrochloric acid with a concentration of 36.5wt% and formaldehyde solution with a concentration of 37wt%, continue to introduce hydrogen chloride gas at 25°C and stir for 10h, filter, wash, and vacuum dry after the reaction to obtain chlorohydroxyquinoline; add Schiff alkalinized chitosan to The mixture was added to an acetic acid solution with a concentration of 5wt% and swelled for 1 hour, and then chlorohydroxyquinoline was added, and the temperature was raised to 80°C for reaction for 20 hours. After the reaction, the pH was adjusted, the mixture was filtered, washed with alcohol, and dried in vacuo to obtain a chitosan corrosion inhibitor. When preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridinecarboxaldehyde was 1:4.3. When preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid, and formaldehyde solution was 1:1.1:1. When preparing the chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline was 1:1.2.
[0038] Cysteine, sodium hydroxide and anhydrous ethanol were mixed, and terephthalaldehyde solution was added dropwise at 30°C, and the mixture was stirred until the solid stopped increasing. After the reaction, the mixture was cooled, washed with alcohol and ground to obtain Schiff-based amino acid. Graphene oxide was mixed with anhydrous ethanol, and after ultrasonic dispersion, γ-methacryloxypropyltrimethoxysilane was added. The mixture was refluxed at 110°C for 10 hours. After the reaction, the mixture was filtered, washed and freeze-dried to obtain modified graphene. The modified graphene, Schiff-based amino acid, 1173 photoinitiator and anhydrous ethanol were mixed and subjected to ultraviolet. The reaction was carried out under light irradiation for 10 minutes. After the reaction was completed, the amino acid corrosion inhibitor was obtained by extraction, drying, filtering, rotary evaporation and vacuum drying. When preparing the Schiff-based amino acid, the reaction molar ratio of cysteine, sodium hydroxide and terephthalaldehyde was 1.9:1:1. When preparing the amino acid corrosion inhibitor, the reaction molar ratio of C=C of the modified graphene and the thiol group of the Schiff-based amino acid was 1:1.7. The amount of the 1173 photoinitiator was 5wt%; wherein the reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane was 0.3:3.
[0039] Chitosan corrosion inhibitor, amino acid corrosion inhibitor, polysulfone and dichloromethane are mixed and stirred to obtain an oil phase; lignin sulfonate is dissolved in water to obtain a 1.8wt% surfactant solution as an aqueous phase, the oil phase is slowly added dropwise to the aqueous phase, and the pre-emulsion is uniformly stirred, and the dichloromethane is evaporated by stirring at 35°C, and the microcapsule corrosion inhibitor is obtained by filtering, washing with water, washing with alcohol, filtering and drying; the microcapsule corrosion inhibitor is added to the dopamine solution, stirred for reaction for 10 hours, and after the reaction is completed, the dopamine microcapsule corrosion inhibitor is obtained by washing with water, washing with alcohol, filtering and drying; the reaction mass ratio of chitosan corrosion inhibitor, amino acid corrosion inhibitor and polysulfone is 1.3:1:1; the pH value of the dopamine solution is 7.5, and the concentration is 1.5g / L;
[0040] Step 2: Add dopamine microcapsule corrosion inhibitor to the preheated epoxy resin, then add curing agent and stir for 20 minutes to obtain epoxy resin coating; take the aluminum profile, grind, alcohol wash, and immerse in dopamine solution for 10 hours, then apply epoxy resin coating and cure at 60°C for 8 hours to obtain the finished product; the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin and curing agent is 0.3:3:1.
[0041] Comparative Example 1: The chitosan corrosion inhibitor was removed, and the rest was the same as Example 1, and the specific steps were as follows: Step 1: Cysteine, sodium hydroxide and anhydrous ethanol were mixed, and a terephthalaldehyde solution was added dropwise at 40°C, and the mixture was fully stirred until the solid no longer increased. After the reaction was completed, the mixture was cooled, washed with alcohol, and ground to obtain a Schiff-basified amino acid; graphene oxide and anhydrous ethanol were mixed, ultrasonically dispersed uniformly, and then γ-methacryloxypropyltrimethoxysilane was added, and the mixture was refluxed at 120°C for 12 hours. After the reaction was completed, the mixture was filtered, washed, and freeze-dried to obtain modified graphene; the modified graphene, Schiff-basified amino acid, 1 173 photoinitiator and anhydrous ethanol are mixed, and the mixture is irradiated with ultraviolet light for 20 minutes. After the reaction is completed, the mixture is extracted, dried, filtered, rotary evaporated, and vacuum dried to obtain an amino acid corrosion inhibitor. When preparing Schiff-based amino acids, the reaction molar ratio of cysteine, sodium hydroxide, and terephthalaldehyde is 1.9:1:1. When preparing the amino acid corrosion inhibitor, the reaction molar ratio of C=C of the modified graphene and the thiol of the Schiff-based amino acid is 1:1.7. The amount of the 1173 photoinitiator is 5wt%. The reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane is 0.3:3.
[0042] The amino acid corrosion inhibitor, polysulfone and dichloromethane are mixed and stirred to obtain an oil phase; lignin sulfonate is dissolved in water to obtain a 1.8wt% surfactant solution as an aqueous phase, the oil phase is slowly added dropwise to the aqueous phase, and the pre-emulsion is uniformly stirred, and the dichloromethane is evaporated by stirring at 40°C, and the microcapsule corrosion inhibitor is obtained by filtering, washing with water, washing with alcohol, filtering and drying; the microcapsule corrosion inhibitor is added to the dopamine solution, stirred for reaction for 15 hours, and after the reaction is completed, the dopamine microcapsule corrosion inhibitor is obtained by washing with water, washing with alcohol, filtering and drying; the reaction mass ratio of the amino acid corrosion inhibitor to the polysulfone is 1:1; the pH value of the dopamine solution is 7.5, and the concentration is 1.5g / L;
[0043] Step 2: Add dopamine microcapsule corrosion inhibitor to the preheated epoxy resin, then add curing agent and stir for 30 minutes to obtain epoxy resin coating; take the aluminum profile, grind, alcohol wash, and immerse in dopamine solution for 15 hours, then apply epoxy resin coating and cure at 70°C for 10 hours to obtain the finished product; the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin, and curing agent is 0.3:3:1.
[0044] Comparative Example 2: The amino acid corrosion inhibitor was removed, and the rest was the same as Example 1, and the specific steps were as follows: Step 1: chitosan was added to an acetic acid solution with a concentration of 5wt% and swelled for 2h, and then a 2-pyridine formaldehyde solution was added, and the temperature was raised to 90°C for reaction for 8h. After the reaction was completed, the pH was adjusted, filtered, washed with alcohol, and vacuum dried to obtain Schiff alkalinized chitosan; 8-hydroxyquinoline, concentrated hydrochloric acid with a concentration of 36.5wt% and formaldehyde solution with a concentration of 37wt% were mixed, and hydrogen chloride gas was continuously introduced at 28°C for stirring and reacting for 12h. After the reaction was completed, the mixture was filtered, washed, and vacuum dried to obtain chloride. Hydroxyquinoline; add Schiff alkaline chitosan to a 5wt% acetic acid solution to swell for 2h, then add chlorohydroxyquinoline, heat to 90℃ and react for 25h, adjust pH, filter, wash with alcohol and vacuum dry after the reaction to obtain chitosan corrosion inhibitor; when preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridinecarboxaldehyde is 1:4.3; when preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid and formaldehyde solution is 1:1.1:1; when preparing chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline is 1:1.2;
[0045] Chitosan corrosion inhibitor, polysulfone and dichloromethane are mixed and stirred to obtain an oil phase; lignin sulfonate is dissolved in water to obtain a 1.8wt% surfactant solution as an aqueous phase, the oil phase is slowly added dropwise to the aqueous phase, and the pre-emulsion is uniformly stirred, and the dichloromethane is evaporated by stirring at 40°C, and the microcapsule corrosion inhibitor is obtained by filtering, washing with water, washing with alcohol, filtering and drying; the microcapsule corrosion inhibitor is added to the dopamine solution, stirred for reaction for 15 hours, and after the reaction is completed, the dopamine microcapsule corrosion inhibitor is obtained by washing with water, washing with alcohol, filtering and drying; the reaction mass ratio of chitosan corrosion inhibitor to polysulfone is 1.3:1; the pH value of the dopamine solution is 7.5, and the concentration is 1.5g / L;
[0046] Step 2: Add dopamine microcapsule corrosion inhibitor to the preheated epoxy resin, then add curing agent and stir for 30 minutes to obtain epoxy resin coating; take the aluminum profile, grind, alcohol wash, and immerse in dopamine solution for 15 hours, then apply epoxy resin coating and cure at 70°C for 10 hours to obtain the finished product; the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin, and curing agent is 0.3:3:1.
[0047] Comparative Example 3: The dopamine microcapsule corrosion inhibitor is removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Add the curing agent to the preheated epoxy resin, stir for 30 minutes, and obtain the epoxy resin coating; take the aluminum profile, grind, wash with alcohol, and immerse in the dopamine solution for 15 hours, then apply the epoxy resin coating and cure at 70°C for 10 hours to obtain the finished product; wherein the reaction mass ratio of the epoxy resin and the curing agent is 3:1.
[0048] Detection test:
[0049] Corrosion resistance test: The finished aluminum profile prepared by the present invention is used as a sample, and the surface grease and moisture of the sample are removed by using filter paper, petroleum ether and absorbent cotton. Then, the sample is immersed in a 1 mol / L hydrochloric acid solution for 1 day. After the immersion, the surface corrosion products are removed, and the sample is washed with alcohol, washed with water, and dried. Finally, the mass of the sample before and after immersion is weighed and substituted into the corrosion rate formula to obtain the corrosion rate.
[0050] Fracture toughness test: The epoxy resin coating prepared by the present invention is poured into a mold of a specific size, cured at 70°C for 10 hours, and then polished to obtain a sample. The test is carried out according to the ASTM D5045 standard, and a prefabricated crack is introduced by tapping a blade at the notch. The sample test uses a 500 N sensor, and the pressure head speed is 10 mm / min. The data is then substituted into the formula to obtain the critical stress intensity factor of the fracture toughness index. The results are as follows:
[0051]
[0052] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the samples have no obvious fluctuations.
[0053] Comparative Example 1: The chitosan corrosion inhibitor was removed, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the corrosion rate increased by 0.0048 g / (m 2 h), the reason is that chitosan corrosion inhibitor can form a multi-layer protective film on the metal surface by combining multiple corrosion-resistant structures, and has excellent comprehensive corrosion resistance. Therefore, after removing the chitosan corrosion inhibitor, the corrosion rate of the sample increases and the corrosion resistance decreases.
[0054] Comparative Example 2: The amino acid corrosion inhibitor was removed, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the corrosion rate increased by 0.0043 g / (m 2 ·h), the critical stress intensity factor of fracture toughness index is reduced to 0.73MPa·m 1 / 2 The reason for analysis is: amino acid corrosion inhibitor has good corrosion resistance, durability and crack resistance. Therefore, after removing it, the corrosion rate of the sample increases, the corrosion resistance decreases, the critical stress intensity factor of the fracture toughness index of the sample decreases, and the fracture toughness decreases.
[0055] Comparative Example 3: The dopamine microcapsule corrosion inhibitor was removed, and the rest was the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the corrosion rate increased by 0.0062 g / (m 2 ·h), the critical stress intensity factor of fracture toughness index is reduced to 0.67MPa·m1 / 2 The reasons are analyzed as follows: dopamine microcapsule corrosion inhibitor contains a variety of corrosion-resistant structures, which can effectively protect the surface of aluminum profiles and improve corrosion resistance; in addition, the graphene structure in the dopamine microcapsule corrosion inhibitor has high strength and rigidity, which can effectively enhance the mechanical properties of the sample, making it less likely to deform and damage when subjected to external forces; therefore, after removing the dopamine microcapsule corrosion inhibitor, the corrosion rate of the sample increases, the corrosion resistance decreases, the critical stress intensity factor of the fracture toughness index of the sample decreases, and the fracture toughness decreases.
[0056] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0057] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength corrosion-resistant aluminum material, characterized in that: The following steps are involved: Step 1: Mix chitosan corrosion inhibitor, amino acid corrosion inhibitor, polysulfone and dichloromethane, stir well to obtain an oil phase; then prepare a surfactant solution as an aqueous phase, slowly drop the oil phase into the aqueous phase, stir evenly to obtain a pre-emulsion, then stir and evaporate dichloromethane at 35-40°C, and filter, wash with water, wash with alcohol, filter and dry to obtain a microcapsule corrosion inhibitor; add the microcapsule corrosion inhibitor to the dopamine solution, stir and react for 10-15 hours, wash with water, wash with alcohol, filter and dry after the reaction to obtain a dopamine microcapsule corrosion inhibitor; Step 2: Add dopamine microcapsule corrosion inhibitor to preheated epoxy resin, then add curing agent and stir for 20-30 minutes to obtain epoxy resin coating; take aluminum profile, grind, alcohol wash, immerse in dopamine solution for 10-15 hours, then apply epoxy resin coating and cure at 60-70℃ for 8-10 hours to obtain the finished product.
2. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step 1, the reaction mass ratio of chitosan corrosion inhibitor, amino acid corrosion inhibitor and polysulfone is (1.2-1.5):1:
1.
3. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step one, the preparation process of chitosan corrosion inhibitor is as follows: chitosan is added to acetic acid solution to swell for 1-2 hours, and then 2-pyridine formaldehyde solution is added, the temperature is raised to 80-90°C for reaction for 6-8 hours, and after the reaction is completed, the pH is adjusted, suction filtration, alcohol washing, and vacuum drying are performed to obtain Schiff alkalinized chitosan; 8-hydroxyquinoline, concentrated hydrochloric acid and formaldehyde solution are mixed, hydrogen chloride gas is continuously introduced at 25-28°C and stirred for reaction for 10-12 hours, and after the reaction is completed, hydroxyquinoline chloride is obtained by suction filtration, washing, and vacuum drying; Schiff alkalinized chitosan is added to acetic acid solution to swell for 1-2 hours, and then hydroxyquinoline chloride is added, the temperature is raised to 80-90°C for reaction for 20-25 hours, and after the reaction is completed, the pH is adjusted, suction filtration, alcohol washing, and vacuum drying are performed to obtain chitosan corrosion inhibitor.
4. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 3, characterized in that: When preparing Schiff alkaline chitosan, the reaction mass ratio of chitosan and 2-pyridine formaldehyde is 1: (4.0-4.5); when preparing chlorohydroxyquinoline, the mass volume ratio of 8-hydroxyquinoline, concentrated hydrochloric acid and formaldehyde solution is 1: (1.0-1.2): 1; when preparing chitosan corrosion inhibitor, the reaction mass ratio of Schiff alkaline chitosan and chlorohydroxyquinoline is 1: (1.1-1.2); the concentration of the acetic acid solution is 3-5wt%; the concentration of the concentrated hydrochloric acid is 36.5-37wt%, and the concentration of the formaldehyde solution is 37-40wt%.
5. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step one, the preparation process of the amino acid corrosion inhibitor is as follows: cysteine, sodium hydroxide and anhydrous ethanol are mixed, terephthalaldehyde solution is added dropwise at 30-40°C, and the mixture is stirred sufficiently until the solid no longer increases. After the reaction is completed, the mixture is cooled, washed with alcohol, and ground to obtain a Schiff-based amino acid; modified graphene, Schiff-based amino acid, 1173 photoinitiator and anhydrous ethanol are mixed, and the mixture is reacted under ultraviolet light for 10-20 minutes. After the reaction is completed, the mixture is extracted, dried, filtered, rotary evaporated, and vacuum dried to obtain an amino acid corrosion inhibitor.
6. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 5, characterized in that: When preparing Schiff-based amino acids, the reaction molar ratio of cysteine, sodium hydroxide and terephthalaldehyde is (1.8-2.0): 1:1; when preparing amino acid corrosion inhibitors, the reaction molar ratio of C=C of modified graphene and the thiol group of Schiff-based amino acids is 1: (1.5-2.0); the amount of the 1173 photoinitiator used accounts for 4-5wt%.
7. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 6, characterized in that: The preparation process of modified graphene is as follows: graphene oxide and anhydrous ethanol are mixed, and after ultrasonic dispersion, γ-methacryloxypropyltrimethoxysilane is added, and reflux reaction is carried out at 110-120°C for 10-12h. After the reaction is completed, the modified graphene is obtained by filtration, washing, and freeze-drying; wherein the reaction mass ratio of graphene oxide and γ-methacryloxypropyltrimethoxysilane is (0.2-0.3):
3.
8. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step 1, lignin sulfonate is dissolved in water to obtain a surfactant solution with a concentration of 1.5-1.8 wt%.
9. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step 1 or step 2, the pH value of the dopamine solution is 7.5-8.0, and the concentration is 1.2-1.5 g / L.
10. The method for preparing a high-strength corrosion-resistant aluminum material according to claim 1, characterized in that: In step 2, the reaction mass ratio of dopamine microcapsule corrosion inhibitor, epoxy resin and curing agent is (0.2-0.3):3:1.
Citation Information
Patent Citations
Schiff base used as corrosion inhibitor for medical magnesium alloys, preparation method of Schiff base and method for preparing self-repairing corrosion-resistant hybrid coating with preparation method
CN110273158A
Method for preparing antifouling anti-corrosion functional microcapsule based on Pickering emulsion
CN110433739A
Preparation method of dioctyl sulfosuccinate / chitosan corrosion inhibitor microcapsule
CN112604613A
Cationic dopamine functionalized graphene water-based anti-corrosive paint as well as preparation method and application thereof
CN113122044A
Preparation method of graphene coating, self-repairing coating and application
CN115873469A
Cited By
Surface hydrophobic corrosion-resistant coating based on copper alloy and preparation method of surface hydrophobic corrosion-resistant coating
CN120173508A